Columnar self-assembly of N, N′, N′′-trihexylbenzene-1, 3, 5-tricarboxamides investigated by means of NMR spectroscopy and computational methods in solution and the solid state. Issue 7 (6th February 2017) - Banach, Ewa; Invernizzi, Christian; Baudin, Mathieu; Neier, Reinhard; Carnevale, Diego
Abstract : The columnar self-assembly resulting from units of N, N ′, N ′′-trihexylbenzene-1, 3, 5-tricarboxamide is investigated in solution and the solid state by means of NMR spectroscopy and DFT methods. Abstract : The columnar self-assembly resulting from units of N, N ′, N ′′-trihexylbenzene-1, 3, 5-tricarboxamide is investigated in solution and the solid state by means of NMR spectroscopy. A parallel computational study utilizing both semiempirical and DFT methods allows comparison between experimental results and calculated data for self-assembled and non-assembled structural hypotheses. The hybrid functional B3LYP is compared with the B3LYP-D and B97D functionals to assess contributions due to dispersion interactions. Interatomic distances are studied utilizing ROE experiments on proton spins in solution. Isotropic shifts as measured experimentally are shown to offer a method to assess the self-assemblies 'on-the-fly'. The anisotropic part of the shift interaction for carbon nuclei is probed in the solid state with specific magic-angle spinning experiments. The sensitivity of the NMR parameters for various carbon environments with respect to the orientation of the substituents and packing effects is investigated computationally. We show that all the utilized experimental techniques, in both solution and the solid state, and in combination with DFT calculations, are capable of discerning between assembled and non-assembled systems and offer a robust set of independent tools to highlight atomic details in self-organized structures.